KAJIAN STATUS KUALITAS AIR KAWASAN PABRIK KELAPA SAWIT (PKS) DI PULAU BANGKA PROVINSI KEPULAUAN BANGKA BELITUNG - Heri Apriyanto (Jurnal Ecolab, 2008)
Industrialization will generate some impacts, and one of these impacts could be related to the negative impacttowards the environment such as pollution. Crude Palm Oil (CPO) industry in Province of Bangka-Belitung Island isone of the primary sectors that promote the local economy after the tin-mining era ended. Meanwhile, to produce theCPO, this process also produce a significant amount of wastewater particularly with high level of BOD and COD.This paper discusse the level of wastewater from CPO mills in Bangka Island and the impact of wastewater towardsthe status of surface water quality within the area. According to the research, though the wastewater has beenprocessed but it still could not accord with the standard of wastewater that permitted by regulation. Consequently,it could pollute the surface water and give a negative impact to the status of water quality.